High-intensity interval training vs. repeated-sprint training in tennis - Fernandez-Fernandez, J.; Zimek, R.; Wiewlhove, T.; Ferrauti, A. (The Journal of Strength and Conditioning Research, 2012)
The aim of this study was to compare the effects of high-intensity interval training (HIIT) and repeated-sprint training (RST) on aerobic fitness, tennis-specific endurance, linear and repeated-sprint ability (RSA), and jumping ability. Thirty-one competitive male tennis players took part in a training intervention of 6 weeks. The players were matched into 3 groups, HIIT (n = 11), RST (n = 12), or control group (CON, n = 9). The results showed significant time × intervention interactions for VO2peak, with a significant increase in the VO2peak level of 6.0% in HIIT (p = 0.008) and 4.9% in RST (p = 0.010), whereas no changes occurred in CON. However, the following differences were found between the intervention groups: The HIIT-induced greater improvements in tennis-specific endurance (HIIT 28.9% vs. RST 14.5%; p < 0.05) and RST led to a significant improvement in RSA (i.e., reduction in the mean sprint time of 3.8%; p < 0.05). Neither training strategy induced any effects on jumping and sprinting abilities. Both training interventions showed similar improvements in general aerobic fitness. Also, the present results suggest that RST represents a time-efficient stimulus for a simultaneous improvement of general and tennis-specific aerobic fitness as well for RSA.